Cosmetic filler-induced hair loss: case series and literature review - Yutong Xie; Xi Chen; Aihua Wei (Journal of Dermatological Treatment)
Aim To present three cases of filler-induced alopecia (FIA) and summarize the current knowledge of its clinical features, mechanisms and treatments.Methods In the first two cases, two females developed well-defined triangular patches of hair loss after hyaluronic acid (HA) injections, and received corticosteriod injections with topical 5% minoxidil. The third case described another female who experienced alopecia areata-like hair loss after autologous fat grafting, and received combined therapies including corticosteriod, 5% minoxidil and microneedling.Results All patients got gradual hair regrowth with treatments.Conclusions Early recognition and intervention are crucial to prevent permanent hair follicle damage. A thorough understanding of frontotemporal anatomy is essential for clinical practitioners to minimize risks during cosmetic procedures involving filler injections.